2019
DOI: 10.1063/1.5049143
|View full text |Cite
|
Sign up to set email alerts
|

Non-orthogonal multi-Slater determinant expansions in auxiliary field quantum Monte Carlo

Abstract: We investigate the use of non-orthogonal multi-Slater determinant (NOMSD) expansions as trial wavefunctions in auxiliary field quantum Monte Carlo simulations of molecular systems. We show that NOMSD trial wavefunctions with as few as twenty determinants are sufficient in order to achieve chemical accuracy across most of the G1 molecular test set. We also show that NOMSD trial wavefunctions are useful for more challenging strongly correlated systems by computing relative energies along the isomerization path o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…The statistical variance in the estimator should not be confused with the wavefunction variance in variational MC. Therefore, it is possible to observe some improvement in the statistical error bar while the energy estimator does not improve noticeably as observed before 32 . This long tail in the convergence of the ph-AFQMC energy is indicative that the system is strongly correlated.…”
Section: Assessment For Lower Densitiessupporting
confidence: 58%
See 3 more Smart Citations
“…The statistical variance in the estimator should not be confused with the wavefunction variance in variational MC. Therefore, it is possible to observe some improvement in the statistical error bar while the energy estimator does not improve noticeably as observed before 32 . This long tail in the convergence of the ph-AFQMC energy is indicative that the system is strongly correlated.…”
Section: Assessment For Lower Densitiessupporting
confidence: 58%
“…AFQMC has been successfully applied in recent years to a number of challenging problems in both quantum chemistry [29][30][31][32][33] and solid state physics [34][35][36] . However, the broad applicability of the method is not as well under-stood as more traditional quantum chemistry approaches which have seen decades worth of sustained development and benchmarking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of unrestricted single determinant trials has been shown to yield sub-kcal mol −1 accuracy for the triplet energies of polyacenes with closed-shell ground-states, and many biradicaloid molecules with open-shell singlet states that can be qualitatively described by two determinants. 53,68 However, some highly multi-reference systems such as transition metal compounds require the use of non-orthogonal determinant expansions 69 or truncated CASSCF trial wavefunctions 55,70,71 to yield high accuracy. In this work, all AFQMC calculations implement unrestricted single-determinant trial wavefunctions selected according to the AFQMC/U protocol, 53 except for those on the BTD and BSeD derivatives, which were found to exhibit signs of strong correlation ( vide infra ) and thus required truncated CASSCF trials.…”
Section: Methodsmentioning
confidence: 99%